Photochemical and Microbial Degradation of Chromophoric Dissolved Organic Matter Exported From Tidal Marshes. Issue 4 (6th April 2021) - Logozzo, Laura; Tzortziou, Maria; Neale, Patrick; Clark, J. Blake
Abstract: Wetlands export chromophoric dissolved organic matter (CDOM) to estuaries, where CDOM is removed and transformed through biotic and abiotic process, subsequently impacting nutrient cycling, light availability, ecosystem metabolism, and phytoplankton activity. We examined the bioavailability and photoreactivity of CDOM exported from four Chesapeake Bay tidal marshes across three seasons and along an estuarine salinity gradient using three incubation treatments: 14‐day microbial (MD), 7‐day combined photochemical/microbial (PB + MD), and 7‐day microbial incubation after photobleaching (MD after PB). CDOM absorption at 300 nm ( a CDOM 300) and dissolved organic carbon (DOC) concentrations showed strong seasonality, with minima in winter, but CDOM quality (absorption spectral slopes, fluorescence component ratios) was less variable seasonally. PB + MD over 7 days decreased a CDOM 300 (−56.0%), humic‐like fluorescence (−67.6%), and DOC (−17.8%), but increased the spectral slope ratio S R (= S 275–295 /S300–350 ) (+94.8%), suggesting a decrease in CDOM molecular weight. Photochemistry dominated the PB + MD treatment. Photoreactivity was greater during the winter and in marsh/watershed versus down‐estuary sites, likely due to less previous light exposure. Prior photobleaching increased the bioavailability of marsh‐exported CDOM, resulting in a greater loss of a CDOM 300 and DOC, and a greater increase in humic‐like fluorescence (−6.0%, −5.9%, and +18.4% change, respectively, over 7‐day MD after PB incubations, vs. −2.8%, −5.5%, and +2.6% change, respectively, over 14‐day MD incubations). CDOM exported from a marsh downstream of a major wastewater treatment plant showed the greatest photoreactivity and bioavailability. This highlights the significance of human activity on estuarine CDOM quality and biogeochemical cycles. Plain Language Summary: Marshes are sources of colored dissolved organic matter (CDOM) to estuaries, where CDOM can be transformed or removed by ultraviolet (UV) radiation or microbes. We examined CDOM susceptibility to UV radiation and microbial degradation from four Chesapeake Bay marshes and along a down‐estuary salinity gradient, using incubation experiments with samples collected in the summer, fall, and winter. Our results showed that although more CDOM is exported by marshes in the summer, the quality of this material (based on optical proxies for CDOM composition) was consistent seasonally and interannually. Microbial processing removed a small, but significant, amount of CDOM and increased the contribution of humic‐like CDOM typically associated with terrestrial sources. Microbial degradation combined with UV exposure decreased the amount of CDOM and the contribution of humic‐like CDOM. Microbial degradation after exposure to UV light resulted in a greater loss of DOC and more production of humic‐like CDOM compared to microbial degradation alone, suggesting exposure to light enhances the microbial utilization of marsh‐exported CDOM. A marsh downstream of a major wastewater treatment plant exported CDOM that was more susceptible to UV and microbial degradation, suggesting that human activity can have significant effects on estuarine biogeochemical cycles, water quality, and ecosystem productivity. Key Points: Marsh dissolved organic matter export showed strong seasonal dependence, but seasonal variability in its quality was significantly lower Exposure to light increased the bioavailability of marsh‐exported chromophoric dissolved organic matter (CDOM) Photobleaching decreased humic‐like CDOM fluorescence, but increased microbial production of humic‐like CDOM fluorescence